Terms and concepts of well-being: review and classification attempt - Karaś, Dominika (Studia Psychologica: Theoria et praxis, 2019)
The main aim of the paper is an attempt to organize an increasing number of definitions of well-being and related concepts, to review the terminology and to present the most popular theories. The manuscript covers two main parts. In the first, the most important theoretical constructs related to well-being are discussed and the relationships between them are shown – as the review of the literature on well-being indicates that often some definitions are unclear, and terminology is often mixed or even confused. The discussed constructs include not only the concept of well-being, but also terms such as happiness, life satisfaction or quality of life. The aim of the article is to show the relationship between these concepts, as well as common and divergent elements between various theoretical approaches. The second part presents selected contemporary concepts of well-being, e.g. the onion theory of happiness, concepts of subjective well-being, three-dimensional concept of well-being, the concept of psychological well-being and eudaimonistic approaches.